2014
DOI: 10.15345/iojes.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Metacognition in Mathematics: Which One of Two Methods is a Better Predictor of Mathematics Achievement?

Abstract: In recent years metacognition was discussed as a significant concept in mathematics education. However, means of measuring metacognition efficiently is still a problem. This problem has been at the center of a scientific debate about which instruments are more suitable. In this study two off-line methods, student and teacher evaluations were used. The aim of this research is to investigate which one of the evaluation form (teacher form versus student form) is the predictor of mathematic achievement. For this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…However, other calculation procedures and indices are possible as well (Boekaerts and Rozendaal 2010;Desender et al 2017), such as the ones that have been used in calibration accuracy and metacognitive monitoring studies (Chen 2002;García et al 1016;Lin et al 2001;Lin and Zabrucky 1998;Schraw et al 2013;2014) to identify correct and/or incorrect performances. This might have given different study outcomes (Desoete 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other calculation procedures and indices are possible as well (Boekaerts and Rozendaal 2010;Desender et al 2017), such as the ones that have been used in calibration accuracy and metacognitive monitoring studies (Chen 2002;García et al 1016;Lin et al 2001;Lin and Zabrucky 1998;Schraw et al 2013;2014) to identify correct and/or incorrect performances. This might have given different study outcomes (Desoete 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although the metacognitive concept is over 40 years old, researchers keep using different definitions for this construct (Baten et al 2017;Brown 1987;Gascoine et al 2017;Perfect and Schwartz 2002;Tarricone 2011). In addition, different evaluators (Ozcan 2014) and techniques to assess metacognition (Desoete 2008;Fleming and Lau, 2014;Sperling et al 2002;Veenman 2011) render studies difficult to compare. A methodical review of the assessment of metacognition for children aged 4-16 years over a 20-year period (1992-2012) revealed that self-report measures (including questionnaires, surveys and tests) comprise 61% of the included tools (Gascoine et al 2017).…”
Section: Cognitive Propensity Predictors For Mathematics Performancementioning
confidence: 99%
“…Another explanation for these results could be related to the distinction between on-line and offline measures, and the low degree of correspondence they show (Özcan, 2014;Veenman, 2011). It is necessary to point out that the use of deep approach to learning and metacognitive knowledge were assessed by means of questionnaires (i.e., offline measures) in the present study, while metacognitive skills were evaluated though the administration of a measure of the process, concurrent to problem-solving performance (i.e., on-line measures).…”
Section: Revista Dementioning
confidence: 91%
“…Problem-solving steps include Understanding the Problem (Understanding the Problem), Making a problem-solving plan (Devising A Plan), Implementing the plan (Carrying Out The Plan), and checking back the results obtained (Looking Back). The conclusion is that the steps in problem-solving are Understanding the problem, Making a problemsolving plan, Implementing the solving plan that has created, Checking back the results that have been obtained or interpreting the results obtained [7].…”
Section: B Problem Solvingmentioning
confidence: 99%